Congenital bronchopulmonary malformation: CT histopathological correlation - Kyncl, Martin; Koci, Martin; Ptackova, Lea; Hornofova, Ludmila; Fabian, Ondrej; Snajdauf, Jiri; Pychova, Marcela (Biomedical papers, 2016)
Background: This study evaluated the accuracy of postnatal computed tomography (CT) imaging in the identification of congenital bronchopulmonary malformation (BPM) in comparison with histopathological analysis. Methods: CT scans of prenatally diagnosed BPMs from 24 patients with available histology were analysed retrospectively. The CT images were reviewed blinded to histological findings by two radiologists. Specific diagnosis was assigned based on predetermined criteria. The accuracy of CT was evaluated. Results: The agreement rate in CT diagnosis between two radiologists was 100%. In 75% the lesions were located in the lower lobes. An overlap of 71% in CT and histopathological diagnoses was reached. The least matching diagnosis was type 2 CPAM. Conclusion: Contrast enhanced chest CT is very accurate in characterizing the BPM spectrum and provides important information on lesion type and structure.
Keywords: bronchopulmonary malformation; computed tomography; histopathological findings; predetermined criteria